Method for producing semiconducting films of organic-inorganic metal-halide compounds with perovskite-like structure - Patents.com

JP7652716B2Active Publication Date: 2025-03-27JOINT CO KRASNOYARSK HYDROPOWER PLANT (JSC KRASNOYARSK HPP)
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021573164
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-06-19
Filing Date
2020-06-16
Publication Date
2025-03-27
Estimated Expiration
2040-06-16

Smart Images

  • Figure 0007652716000002
    Figure 0007652716000002
  • Figure 0007652716000003
    Figure 0007652716000003
  • Figure 0007652716000001
    Figure 0007652716000001
Patent Text Reader

Abstract

The present invention relates to the field of materials science, in particular to a method for producing films of semiconducting materials based on organic-inorganic metal-halide compounds with a perovskite-like structure that can be used as light-absorbing layers in solar cells, such as thin-film, flexible, tandem solar cells, and can also be applied to optoelectronic devices, in particular light-emitting diodes. 1. A method for producing a semiconductor film of an organic-inorganic metal-halide compound having a perovskite-like structure, the method comprising the steps of: (a) applying a layer of a precursor of component B onto a substrate; (b) applying a layer of a composite reagent onto the surface of the precursor layer of component B; and (c) treating the layer applied on the substrate with a reagent X2 for a time necessary and sufficient for the completion of a chemical reaction between the applied reagent and the precursor of component B, thereby resulting in the formation of an organic-inorganic metal-halide perovskite-like compound, wherein the composite reagent applied in step b) comprises a mixture of an AX reagent and an X2 reagent, the [X2] / [AX] molar ratio being in the range of 0<[X2] / [AX]<1, and the film obtained after step b) comprises seeds of a phase having a perovskite-like structure, and component B comprises cations M of different metals (e.g., Pb, Sn, Bi) selected from Pb, Sn, Bi, and mixtures thereof. n+ Reagent AX contains cation A + and anion X - A salt containing cation A + But methylammonium CH3NH3 + , formamidinium(NH2)2CH + , guanidinium C(NH2)3 + , Cs + , Rb + and unsubstituted (NH4 + ) or a substituted ammonium cation, such as a mono- or di- or tri- or tetra-substituted ammonium cation, and combinations thereof; an anion X - But Cl - , Br - , I -or pseudohalide anions, and combinations thereof, and the reagent X2 is a molecular halogen. The present invention provides a simpler and more efficient method for producing thin films of semiconductor films of organic-inorganic metal-halide compounds with perovskite-like structures, which can be used as light-absorbing layers in perovskite solar cells, ensuring improved efficiency compared to analogues.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of materials science, in particular to a method for producing films of semiconducting materials based on organic-inorganic metal-halide compounds with a perovskite-like structure that can be used as light absorbing layers in solar cells, such as thin film, flexible, tandem solar cells, and can also be applied to optoelectronic devices, in particular light emitting diodes. [Background technology]

[0002] Several methods are previously known for preparing semiconducting films of light-absorbing materials with perovskite-like structures.

[0003] The preparation of thin layers or films of perovskite CH3NH3PbI3 in one step by applying a solution of organic mixed solvents containing perovskite on a substrate with a thin layer by rotating at high speed around an axis perpendicular to the layer plane is described in reference [Saliba M.et al.Incorporation of rubidium cations into perovskite solar cells improves photovoltaic performance / / Science(80-.).2016.Vol.354,No6309.P.206-209.]. In this case, the obtained perovskite film is integrated with other layers in the composition of the solar cell and serves as a light absorbing material. In particular, this document describes the fabrication of perovskite solar cells consisting of five main functional layers coated on a glass substrate: a transparent conductive electrode (e.g., FTO), an electron transport layer (e.g., TiO2 blocking layer), a light absorbing layer (perovskite), and a hole transport layer (e.g., Spiro MeOTAD), and a counter electrode (Au). Light is absorbed by the perovskite layer, and non-equilibrium charge carriers (electrons and holes) are formed in it. Further, the electrons and holes are transferred to the electron transport layer and hole transport layer, respectively, and further to the corresponding electrodes.

[0004] The drawback of the above method is that it is difficult to prepare perovskite layers from solution on large area substrates, and therefore it is not possible to fabricate large area perovskite solar cells. Known documents of particular relevance to the claimed invention are: International Publication No. 2018124938 (A1) "Methods for producing light-absorbing materials with perovskite structure and liquid polyhalides of variable composition for their implementation", Russian Patent Application Publication No. 2685296 "method for producing a film of light-absorbing material with a perovskite-like structure", and Russian Patent Application Publication No. 2675610, entitled "A method for producing a film of a light-absorbing material with a perovskite-like structure."

[0005] The method described in WO2018124938A1 consists of mixing a reagent of composition AX-nX2, where n is 1 or more, component A is a monovalent organic or inorganic cation or a mixture thereof, and component X2 is Cl2, Br2, I2, or a mixture thereof, with a reagent containing B, which is used as a film of a given thickness of Sn, Pb or Bi in the form of a metal, or an alloy, oxide, salt. The reagent composition AX-nX2 is applied to the reagent B, and the reaction proceeds as follows: B+AX+X2=ABX3, obtaining the perovskite ABX3, and optionally removing the excess of the reagent.

[0006] A disadvantage of the known method is the impossibility of dosing a stoichiometric amount of polyiodide (polyhalide) reagent with respect to component B per unit area of ​​film. The impossibility of dosing is a consequence of the high reactivity and viscosity of the liquid composition AX-nX2. Any significant (more than 5%) difference in the AX3 / B ratio from the stoichiometric ratio corresponding to pure ABX3 will inevitably lead to a deterioration in the quality of the film of semiconductor material obtained (in particular the thickness uniformity and phase purity), which will have a negative effect on the efficiency of the solar cell based on the film obtained.

[0007] In the method described in RU 2685296 C1, a homogeneous layer of component B is formed on a substrate, a mixture of a reagent that reacts with component B and a reaction inhibitor that inhibits this reaction under these defined conditions is prepared, the prepared mixture is applied to the layer of component B in a stoichiometric or superstoichiometric amount, and the reaction inhibitor is removed from the mixture, so that a chemical reaction between the mixture of reagents and component B is activated to form a film of a perovskite-like material (ABX3).

[0008] The above method allows the formation of perovskite layers on surfaces of virtually any size. However, the drawback is the low efficiency of the films obtained using this method (less than 5%). [Stepanov NM, Petrov AA, Belich NA, Tarasov AB, Study of the reactivity of the ternary system MAI-I2-i-PrOH with metallic lead to obtain MAPbI3films(MA=CH3NH3), the conference XXV International Conference of Students, Graduate Students and Young Scientists, "Lomonosov", abstract, Russia, April 9-13, 2018], [Rakita Y.et al.Metal to Halide Perovskite(HaP):An Alternative Route to HaP Coating,Directly from Pb(0)or Sn(0)Films / / Chem.Mater.2017.Vol.29,No.20.P.8620-8629]. This problem is the result of fundamental deficiencies inherent in this method, in particular: 1) precise control of the conditions and rate of the process of forming the perovskite layer is hardly achievable with the above methods, and therefore the morphology and size of the particles and crystallites of the obtained perovskite film. This problem is caused by the high reactivity of the AX-nX2 compositions of the polyiodide melt formed upon removal of the inhibitor, and their increased recrystallization ability for the perovskite layer. 2) Cesium and formamidinium (FA + Phase separation during the formation of mixed-cation perovskites containing δ-CsPbI3, δ-FAPbI3 due to chemical conversion processes at low temperatures that irreversibly form non-perovskite low-temperature phases, e.g., δ-CsPbI3, δ-FAPbI3.

[0009] From the point of view of technical essence, the method for producing a film of a light-absorbing material with a perovskite-like structure having the structural formula ADE3 (in the terminology of the claimed invention, component D is identical to component B and component E is identical to component X) disclosed in Russian Patent Application Publication No. 2675610 is the most relevant to the claimed invention. This method is realized by successively applying a layer of reagent D and a layer of reagent AE to a substrate. The substrate with the deposited layer is then placed in a liquid or gaseous medium containing reagent B2 for a period of time necessary and sufficient for the reaction to proceed: C+AE+E2=ADE3+X, CH3NH3 + or (NH2)2CH + or C(NH2)3 + or Cs + or mixtures thereof are used as component A, Cl or Br is used as component E or I or mixtures thereof, Sn, Pb or Bi metal or alloy or oxide or salt thereof serves as component D, and X represents a decomposition product of component D when the oxide or salt is used as component D.

[0010] The main drawback of the above methods is the difficulty in controlling the deposition of a layer of reagent AE on the substrate surface carrying a layer of component D. In particular, in the case of organic cation A, deposition of thin layers of AE reagents by gas phase or thermal evaporation methods is difficult due to the possibility of their thermal decomposition and uncontrolled deposition in areas of the substrate where such deposition is undesirable or unacceptable.

[0011] High dosages of Reagent AE per unit area can be achieved by using vacuum deposition to apply Reagent AE, but requires the use of expensive equipment.

[0012] Furthermore, the bilayer structure AE@D formed by any of the possible methods exhibits a very high sensitivity to air moisture due to the high moisture sensitivity (hygroscopicity) of the AE reagents, the latter requiring the use of special conditions, technical measures and solutions when handling the resulting bilayer structure.

[0013] These two factors significantly reduce the technical merit of this approach for the large-scale production of perovskite thin films and devices based on them.

[0014] Terminology of the present invention In the context of the present invention, a perovskite-like structure refers to both a perovskite structure and any structure derived from the perovskite structure. Thus, the terms "perovskite-like compound" and "perovskite-like phase" as used herein refer to compounds and phases having a perovskite-like structure, respectively.

[0015] In particular, the term "halide perovskite" in the context of the present invention refers to a phase having the formula ABX3 with a cubic crystal system or any lower crystal system (e.g., tetragonal, orthorhombic), as well as a mixture of different phases of halide perovskites. The structure of a halide perovskite is characterized by the central atom - component B (cation B n+ ) and six X atoms (anion X - ) at their corners.

[0016] In particular, the term "perovskite-like structure" as used herein refers to a set of structures of so-called layered or two-dimensional or low-dimensional perovskite-related compounds that contain layers (perovskite layers) of corner-connected octahedra [BX6] alternating with layers of another motif (e.g., Aurivillius phase, Ruddlesden-Popper phase, Dion-Jacobson phase) [Mitzi DBSynthesis, Structure, and Properties of Organic-Inorganic Perovskites and Related Materials / / Progress in Inorganic Chemistry, Volume 48. Wiley Online Library, 2007. P. 1-121]. Perovskite-like compounds and perovskite-like phases refer to compounds and phases having a perovskite-like structure, respectively.

[0017] The above-mentioned halide perovskites and halide perovskite-like phases belong to the complex halide salts including haloplumpates, halostannates and halobismuthates (complex metal halide salts of lead, tin and bismuth, respectively), and therefore such materials are generally referred to as organic-inorganic metal-halide compounds with perovskite-like structures.

[0018] The term "seed" as used herein refers to small particles or nuclei of crystallites of a perovskite-like phase having a size in any dimension of 100 nm or less. [Prior art documents] [Patent documents]

[0019] [Patent Document 1] International Publication No. 2018124938 [Patent Document 2] Russian Patent Application Publication No. 2685296 [Patent Document 3] Russian Patent Application Publication No. 2675610 [Non-patent literature]

[0020] [Non-Patent Document 1] Saliba M.et al.Incorporation of rubidium cations into perovskite solar cells improves photovoltaic performance / / Science(80-.).2016.Vol.354,No6309.P.206-209. [Non-Patent Document 2] Stepanov NM,Petrov AA,Belich NA,Tarasov AB,Study of the reactivity of the ternary system MAI-I2-i-PrOH with metallic lead to obtain MAPbI3 films(MA=CH3NH3),the conference XXV International Conference of Students,Graduate Students and Young Scientists, "Lomonosov",abstract,Russia,April9-13,2018 [Non-Patent Document 3] Rakita Y.et al.Metal to Halide Perovskite(HaP):An Alternative Route to HaP Coating,Directly from Pb(0)or Sn(0)Films / / Chem.Mater.2017.Vol.29,No.20.P.8620-8629 [Non-Patent Document 4] Mitzi DBSynthesis,Structure,and Properties of Organic-Inorganic Perovskites and Related Materials / / Progress in Inorganic Chemistry,Volume48.Wiley Online Library,2007.P.1-121 Summary of the Invention [Problem to be solved by the invention]

[0021] The technical problem is the need to overcome the inherent shortcomings of known analogues and prototypes by inventing simpler and more technologically advanced methods for producing semiconducting films of organic-inorganic metal-halide compounds with perovskite-like structures that can be used as light absorbing layers in perovskite solar cells to improve the power conversion efficiency (PCE or efficiency) compared to their analogues.

[0022] The technical result achieved by using the claimed invention is that the introduction of the intermediate step and the initial reagent AX and the precursor of component B (hereinafter "precursor B") resulting in the formation of a film containing seeds of a phase with a perovskite-like structure allows the formation of a film of a perovskite-like phase with an increased average grain size compared to related methods, which ensures an increase in the efficiency (PCE) of the solar cell based on the film of perovskite-like material obtained as light absorbing layer.

[0023] An additional technical result is the improved electronic and optical properties of the perovskite films obtained using the proposed method compared to related methods involving reactive conversion of a component precursor B by the action of reagents AX and X2 into organic-inorganic metal-halide compounds with perovskite-like structures.

[0024] Another advantage of the proposed method is its feasibility without the use of special expensive equipment and complex technical requirements, which makes the claimed method more suitable for use in industrial large-scale production. [Means for solving the problem]

[0025] The formation in the intermediate step of the film, including seeds of a phase having a perovskite-like structure, as well as the initial reagents AX and precursor B, is necessary to increase the particle size in the resulting film of an organic-inorganic metal-halide compound having a perovskite or perovskite-like structure. The increase in particle size improves the electronic and optoelectronic properties of the film of the polycrystalline semiconductor material, and in particular, leads to a reduction in the recombination of charge carriers at grain boundaries, which results in an improvement in the efficiency (PCE) of devices based on films of the same material with larger particles (see Table 1 in the Examples section of the present invention). When a film containing seeds of a phase having a perovskite-like structure, as well as the initial reagents AX and precursor B, is treated with a halogen, the seeds grow by consuming the initial reagents AX and precursor B and other seeds through a chemical reaction between the reagent AX, precursor B, and X2 (e.g., B + AX + X2 = ABX3, etc.), thereby finally resulting in a film of a perovskite-like phase having large particles (average diameter of 500 nm or more). The treatment with halogen is carried out at a specific temperature and specific partial pressure (or specific concentration) of the halogen, which brings about control of the chemical reaction rate and particle size of the perovskite film, and can surely overcome the drawbacks of analogs and prototypes.

[0026] In the context of the present invention, chemical conversion means a chemical process that results in the formation of a halide perovskite ABX3 or a halide perovskite-like compound A n+1 BnX 3n+1 (where 1 < n < 100). In the general case, the reaction can be represented by the following equation: nB`+(n + 1)AX+((3n + 1) / 2)X2 = A n+1 B n X 3n+1 +Y, where B`- is the precursor of component B, and Y- is the by-product released when an oxide or salt is used as the precursor of component B.

[0027] Chemical conversion can occur as a result of both simultaneous and multiple sequential additions of the components. In the context of the present invention, complete chemical conversion of the initial reagents (AX, X2) and precursors (B) to organic-inorganic metal-halide compounds with perovskite-like structures means that more than 90% (molar fraction) of the initial materials (reagents and precursors) have reacted. [Brief description of the drawings]

[0028] [Figure 1] Figure 1(a) (left) shows a micrograph of the surface of the film using a scanning electron microscope (SEM). Figure 1(a) (left) shows a micrograph of the surface of the film obtained after applying to the surface of metallic lead (precursor of component B) a solution containing a mixture of reagents MAX and X2 in the ratio [X2] / [MAX] = 0.5. On the surface of the film, perovskite particles MAPbI3 and MAI with a size of about 20-100 nm can be seen. Figure 1(b) (right) shows a micrograph of the surface of the final perovskite film obtained after treatment of the film shown in Figure 1(a) with iodine (X2) vapor and after complete chemical conversion to the perovskite MAPbI3. The obtained film contains crystallites with a size of 200 nm to more than 1 μm. [Diagram 2] FIG. 1 shows a graph reflecting the dependence of the average grain size of the obtained MAPbI3 perovskite films on the composition of the solution used to form the intermediate film in step II, and the PCE (%) of the solar cells containing the films fabricated using these perovskite films as light absorbing layers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] The method for producing semiconducting films of organic-inorganic metal-halide compounds with perovskite or perovskite-like structure according to the present invention is a process comprising the following main steps:

[0030] Step-I: Form a precursor layer of component B, where B=Pb, Sn, Bi on the substrate surface.

[0031] Step II: Molar ratio 0.5<[A+ ] / [X - ]<10 Component A + and X - or a mixture of 0 < [X - A composite reagent comprising a mixture of reagent AX and reagent X2 with the range of 0<[X2] / [X2]<1 or 0<[X2] / [AX]<1 is applied on the surface of the precursor layer of component B to form a seed of a perovskite-like phase as well as a film comprising components AX and B. This step can include an additional step of post-processing (heating, annealing, light irradiation) the obtained film without changing its chemical composition.

[0032] Step III: Treat the perovskite or perovskite-like seeds and the preformed film containing reagent AX and the precursor of component B with reagent X2 ( exposure ) to form a semiconducting film of an organic-inorganic metal-halide compound with a perovskite or perovskite-like structure, or a film of a material having the same composition as the target phase of an organic-inorganic metal-halide compound with a perovskite or perovskite-like structure, or a mixture thereof. In the last two cases, an auxiliary step of post-processing of the resulting film of material is introduced to ensure the complete conversion of any impurity phase of the film material to the target phase of an organic-inorganic metal-halide compound with a perovskite or perovskite-like structure.

[0033] In the first step (step I), a layer of the precursor of component B is formed on the surface of a carrier substrate. In this case, glass, transparent conductive silicon oxide, polymers such as transparent and conductive polymers, and any other material that is inert to the reagents and final materials (perovskite halides or perovskite-like compounds) used are used as carrier substrates. Experiments have shown that the physicochemical processes occurring in all three main steps of the proposed process do not depend on the nature of the inert material of the carrier substrate. An inert material in the terms of the claimed invention is any material that does not undergo any chemical interaction with the final material, its components, reagents and solvents used in its synthesis. Hereinafter, the substrate material will be referred to as the material of the top layer of the substrate, onto which the precursor of component B is directly applied.

[0034] In one embodiment of the present invention, the carrier substrate material is selected to be the same as that used in the construction of perovskite solar cells and similar photovoltaic devices. Typically, in such devices, the ABX3 layer is applied on top of a layer of transparent electronically conductive material (transparent conductive oxide, conductive polymer) that is deposited on top of glass or a transparent polymer. In the general case, it is assumed that the carrier substrate contains all the functional layers required to make a finished device (solar cell, LED), except for the layer of light absorbing material ABX3 and the functional layers above it.

[0035] In one embodiment of the present invention, layers of lead, tin or bismuth with thicknesses between 5 nm and 500 nm were sprayed onto substrates of the following materials: fluorine-doped tin oxide (FTO) glass doped with indium tin oxide (ITO), tin oxide SnO2 (FTO, on ITO) or titanium oxide TiO2 (planar and mesoporous layers), polyethylene terephthalate, polytriarylamine (PTAA).

[0036] Before applying the precursor layer of component B, the surface of the carrier substrate is thoroughly cleaned of contaminants: in particular, it is purified with an aqueous solution of a surface-active substance (surfactant) using ultrasound, washed with distilled water and purified with ozone plasma.

[0037] The precursors of component B are applied in the form of metal films - Pb, Sn, Bi or their alloys, or layered structures containing multiple layers of stacked metals (Pb, Sn, Bi). Also, lead salts and oxides, such as PbI2 and PbO, can be used as precursors of component B.

[0038] The precursor of component B is applied by vacuum deposition, electrochemical deposition, chemical vapor deposition, decomposition, or other methods of a previously applied solid phase compound containing component B.

[0039] The most convenient and technologically advanced is the use of metal component B as a precursor. Methods for applying metal films of a given thickness are well known, widely distributed and available.

[0040] In one embodiment, films of component B precursors in the form of metals (tin, lead, bismuth) were deposited by thermal or magnetron sputtering in vacuum while the cleaned substrate was placed in the vacuum chamber and sputtered at a fixed distance from the heated crucible or magnetron target, with the thickness of the sprayed coating controlled by a quartz thickness sensor.

[0041] In the second step (step II), a composite reagent is applied to the surface of the precursor layer of component B, and the composite reagent has a conductivity of 0.5<[A + ] / [X - ]<10 molar ratio of component A + and X - or a mixture of 0<[X - A perovskite-like phase seed is formed containing reagent AX and reagent X2 in the range of 0<[X2] / [AX]<1 or 0<[X2] / [AX]<1, and a film is formed containing reagent AX and precursor B.

[0042] Reagent AX or Component A + and X -The mixture of and the composite reagent including reagent X2 is distributed in a uniform thin layer on the surface of the precursor layer of component B using inkjet printing, screen printing, spin coating, and dip coating aerosol spraying methods, in particular ultrasonic spraying, spraying through a nozzle, electrospraying, aerosol inkjet printing or other methods.

[0043] As a complex reagent, cation A + , anion X - and halogen X2, as well as colloids or suspensions or emulsions containing these components in the liquid or solid phase in a mixture with one or more solvents.

[0044] Add component A to the composite reagent composition in the required stoichiometric ratio. + and X - To add the component A, it is possible to use both the AX salt itself and any mixture of salts, at least one of which is + and any other components X - As a result of mixing, the composition of the solution contains Component A. + and X - In one embodiment of the present invention, composite reagents were prepared using acetates, formates, fluorides, oxalates of monovalent organic cations mixed with ammonium, potassium or hydrogen halides as the halide anion source, the organic cation salt and the anion halide source being in near unitary ratios.

[0045] In one embodiment of the present invention, methylammonium iodide (CHNHI), methylammonium bromide (CHNHBr), formamidinium iodide (FAI), formamidinium bromide (FABr), cesium iodide (CsI) and various halide salts of substituted (primary, secondary, tertiary, or quaternary) ammonium cations and other stoichiometric halides containing suitable monovalent cations were used as AX salts.

[0046] For successful implementation of the proposed method, the concentrations of reagents AX and X2 in the applied composite reagent are selected to ensure that a stoichiometric amount of component A is applied relative to component B per unit area of ​​membrane.

[0047] This condition is met in particular when the precursor component A of the reagent AX is applied to the membrane surface in a stoichiometric amount per unit area of ​​the membrane, in which case deviations of up to 10% from the optimal A / B ratio of the resulting material can be tolerated.

[0048] For 3D halide perovskites, the optimal A / B ratio is 1, as this corresponds to the stoichiometry of the final material ABX3, resulting in a single-phase film after the conversion is complete. For other perovskite-like compounds, this ratio may vary depending on the desired compound. In particular, an A / B ratio = (n+1) / n was shown to be optimal for layered halide perovskites.

[0049] In one embodiment, the layered halide perovskites BA2PbI4, PEA2PbI4, BDAPbI4 (BA + is a butylammonium cation, and PEA + is the phenylethylammonium cation, BDA 2+ is the butanediammonium cation) was obtained with an optimal A / B ratio of about 2. Similarly, the optimal A / B ratio of any perovskite-like compound can be easily calculated according to its chemical formula.

[0050] The most convenient and technically simple way to apply a certain amount of reagents AX and X2 per unit area of ​​the film of precursor B is to dispense their solutions on the surface of the precursor layer of component B. In this case, acetone, alcohol, tetrahydrofuran, dioxane, acetonitrile or mixtures of these solvents in any ratio are used, as well as any other organic or inorganic neutral solvent. In this context, a neutral solvent is any solvent that is not capable of dissolving the compound of component B at a concentration of more than 0.3 M.

[0051] In different embodiments of the present invention, the composite reagent comprising reagents AX and X2 can be applied onto the substrate by any means. Typically, to distribute a thin layer of reagents AX and X2 uniformly over the entire surface of the substrate, spin-coating method is convenient due to its fast distribution and small amount of solution required. Generally, for a large-area substrate, the composite reagent is applied onto the substrate by spin-coating, spray-coating (aerosol spray), slot-die coating, or deposition.

[0052] For the successful realization of the claimed method, it is necessary to obtain a film after step II that not only has an A / B ratio corresponding to the chemical formula of the desired perovskite-like compound, but also contains seeds of a perovskite-like phase (perovskite phase nuclei), as well as residual reagents AX and precursor B.

[0053] A fundamentally important condition for the formation of perovskite phase nuclei is the possibility of forming a perovskite by chemical reaction of the reagent solutions AX and X2 with the precursors of component B. In this case, it is necessary to chemically convert only a portion of the initial precursors of component B into perovskite, leaving a portion of it unchanged to react with the excess of the applied reagent AX during the treatment with halogen in the next step (III) with the formation of the perovskite.

[0054] The amount of perovskite-like phase in the form of seeds after step II is determined by the amount of halogen X2 in the applied composite reagent. For this reason, the process is carried out under conditions such that only a chemical reaction (chemical conversion) of the component B precursor into perovskite occurs when interacting with the reagents AX and X2, and no perovskite is formed when the component B precursor interacts with AX. These conditions are realized because the reagents AX and X2 together form a highly reactive polyiodide melt [Petrov AAet al.A new formation strategy of hybrid perovskites via room temperature reactive polyiodide melts / / Mater.Horiz.2017.Vol.No.4.P.625-632], which reacts with the precursor of component B to form perovskite in a few seconds or tens of seconds at low temperatures, while the reaction of component B with the reagent AX proceeds with a noticeable speed only at high temperatures or within hours.

[0055] Thus, when a stoichiometric amount of AX is applied to the precursor of component B, the amount of perovskite is determined by the ratio [X2] / [AX] or the ratio of halogen-δ.

[0056] Therefore, the general equation for the chemical process occurring in step II can be written as follows: B`+AX+δX2→δABX3+(1-δ)B``@AX+Y↑ where B' is the initial precursor of component B (usually in metallic form), B'' is the final precursor of component B (not a perovskite or perovskite-like compound), usually the same as the original precursor B', and Y is a by-product (which can then be removed in post-processing). Pb+MAI+δI2→δMAPbI3+(1-δ)Pb@MAI {Pb 0.8 Sn 0.2}+MAI+δI2→δMAPb 0.8 Sn 0.2 I3+(1-δ){Pb 0.8 Sn 0.2}@MAI Pb+2BAI+δI2→δBA2PbI4+(1-δ)Pb@2BAI

[0057] In one embodiment of the present invention, an organic solvent solution containing reagents AX and X2 is applied to the surface of the component B precursor by spin-coating (or spin-coating) the organic solvent with spin-coating to form a film containing nuclei of particles of the halide perovskite phase. In the process of spin-coating (e.g., -Paper (http: / / konf.x-pdf.ru / 18fizika / 632895-1-fotovoltaicheskie-strukturi-osnove-organicheskih-poluprovodnikov-kvantovih-tochek-cdse.php); -GOST R ISO 27911-2015 "State system for ensuring the uniformity of measurements (GSI).Chemical analysis of the surface.Scanning probe microscopy.Determination and calibration of the lateral resolution of a near-field optical microscope" (http: / / docs.cntd.ru / document / 1200119068); - https: / / www.msu.ru / science / main_themes / v-mgu-razrabotali-novuyu-strategiyu-polucheniya- perovskitnykh-solnechnykh-yacheek.html), the solution is distributed uniformly in a thin layer on the surface, and as soon as the evaporation of the solvent begins, the concentration of the reagents AX and X2 in the thin layer above the film of the precursor of component B increases and a rapid chemical reaction of AX and X2 with the precursor of component B begins. If the [X2] / [AX] ratio is greater than 0 and less than 1, the result will be nuclei of particles of perovskite phase or perovskite-like phase, as well as a film containing AX and B. The film is achieved in a time of the order of 5-100 seconds, if the process is carried out at temperatures of 10-40 ° C. In the absence of X2, no perovskite formation occurs under these conditions, but when [X2] / [AX] is greater than 1, the reaction leads to complete conversion of component B by the precursor to a halide perovskite.

[0058] Thus, the key step of the proposed method (the formation of perovskite or perovskite-like nuclei and a film containing reagent AX and precursor B) can be achieved when the ratio [X2] / [AX] is in the range of >0 <1. This optimal ratio is close to 0.5 (see the Examples section and Table 1 of the present invention).

[0059] In the special case of the invention, the film obtained in step II can be subjected to additional post-processing treatments. Post-processing treatments can consist of annealing (heat treatment), treatment in an atmosphere of a specific composition (inert gas, dry air, moist air, solvent fume), irradiation with visible, ultraviolet or infrared light. Post-processing treatments are carried out to remove residual solvents or other auxiliary reagents, to remove possible by-products of the reaction forming halide perovskite (or perovskite-like compounds), and to complete the desired reaction to the desired degree of progression. In most cases, in the implementation of the invention, the post-treatment of step II consists of a short-term (1-3600 s) annealing at a given temperature (30-300° C.).

[0060] In a third step (Step III), the formed film containing the perovskite or perovskite-like phase particle embryos and reagents AX and B is processed with X2 until the precursor of component B and reagent AX are completely reacted to produce a film of a halide material with a perovskite or perovskite-like structure.

[0061] In one embodiment, the treatment with X2 (halogen) or "halogenation" is carried out in the gas or liquid phase. In the first case, halogen vapor is used, in the second case, a neutral solvent solution containing the halogen is used. In this context, a neutral solvent is understood to mean any solvent that does not dissolve or chemically interact with the final material (for example the perovskite ABX3) and does not dissolve or chemically interact with the reagents AX and precursor B.

[0062] In one embodiment, alkanes (heptane, octane, decane), haloalkanes (chloroform, dichloromethane), toluene, chlorobenzene, ethers and esters, as well as other slightly polar or non-polar solvents, and any mixtures thereof, are used as solvents for the halogen X2. In principle, any aprotic solvent can be used, since it has been experimentally shown that the nature of the aprotic solvent does not affect the chemical transformation of the precursors of reagent AX and component B when the halogens are exposed to halide perovskite or perovskite-like phases.

[0063] In one embodiment, halogenation from the gas phase is carried out at room temperature in an atmosphere of air or a neutral gas in a sealed thermostatic vessel in which the film formed in step II is placed.

[0064] During the treatment of the film formed in step II with halogen (X2), the reagent AX and precursor B contained in the film react with the halogen in advance near the perovskite-like seeds, resulting in the growth of the perovskite-like phase and the formation of large perovskite-like grains (typically larger than 500 nm). In general, "large grains" of polycrystalline thin films are defined herein as grains whose average grain size is equal to or greater than the film thickness. The optimal thickness of the perovskite-like film is in the range of 200-1000 nm, which typically ensures that the film absorbs more than 90% of the incident light.

[0065] The optimum conditions of chemical conversion to obtain a film of halide perovskite of a given composition and thickness were selected by varying the process temperature and time (chemical conversion time), as well as the pressure of the halogen vapor or the halogen concentration in the solution. In different embodiments of the invention, the parameters were varied as follows: temperature from 0 to 300°C, process time from 5 seconds to 3600 seconds, partial pressure of halogen vapor from 0.01 mmHg to 500 mmHg (see Table 1).

[0066] Processing with halogen at a given temperature and a given halogen partial pressure (or concentration in the case of solutions) allows the influx rate of the halogen to the film surface to be set, and therefore the conversion reaction rate and the grain size of the perovskite film formed. Increasing the temperature and / or partial pressure leads to an acceleration of the conversion reaction. The crystallite size increases with increasing duration of the conversion reaction. However, starting from a certain processing time when complete conversion of the film has already been achieved, further processing can lead to a deterioration of the morphology and optoelectronic properties of the perovskite halide film.

[0067] During treatment with halogen X2, the formation of reactive polyhalide melts occurs according to the reaction AX + nX2 → AX 2n+1It should be noted that the formation of hybrid perovskites occurs according to [Petrov AA et al. A new formation strategy of hybrid perovskites via room temperature reactive polyiodide melts / / Mater.Horiz.2017.Vol.4,No.4.P.625-632.]. The polyhalide melt facilitates the chemical conversion of the precursor of component B to a halide perovskite or perovskite-like phase. An important feature of the proposed method is the ability to control the rate of halogen influx into the film containing the reagents and components required for reactive formation in the presence of halogen perovskite or perovskite-like compounds. In this case, the perovskite formed by the reaction B + AX ​​+ X2 = ABX3 does not form a large number of small crystallites or particles, but does result in the growth or reactive growth of small perovskite phases present in the halogen-treated film. Thus, the entire process carried out in the second and third steps of the proposed method can be reflected by the following equation in the case of halide perovskites: B`+AX+δX2→δABX3+(1-δ)B``@AX+Y↑(Step-II) {δABX3+(1-δ)B``@AX}+X2→ABX3(Step-III) Here, the reagents shown in curly brackets {} are part of the membrane formed in the second step.

[0068] Thus, in contrast to the method described in RU 2685296 C1, the claimed solution leads to a delay in the formation of halogenated perovskite during the chemical transformation with halogen, contributing to the possibility of the crystallites growing to a larger size, and a necessary condition for this is the formation of a film of said composition in the second (intermediate) step of the perovskite film formation. Due to the slow formation of perovskite and therefore the slow growth of the crystals under near-equilibrium conditions, not only can films with large crystallites be produced, but also the concentration of defects in the crystals is low.

[0069] In one embodiment of the present invention, the halide perovskite or perovskite-like phase film after completion of the chemical transformation under the influence of the halogen undergoes additional post-processing treatments. Post-processing treatments may include annealing (temperature treatment), treatment in an atmosphere of a specific composition (inert gas, dry air, moist air, solvent vapor), irradiation with visible, ultraviolet or infrared light, and treatment with a solution or solvent of a desired composition. Post-processing treatments are carried out to remove excess halogen adsorbed by the film, to remove possible by-products of the chemical transformation, or to improve the functional properties of the perovskite layer.

[0070] In one embodiment, during a long reaction treatment with halogen (5 minutes or more), a post-treatment consisting of annealing the film at a given temperature or a specific temperature range, or at a pressure above the film lower than atmospheric pressure, or simultaneously using the effects shown, was used to remove the excess of halogen X2. Furthermore, the higher the temperature and the lower the pressure, the higher the halogen removal rate. The optimal post-processing temperature for this material is the temperature that ensures the rapid removal of the halogen excess (in less than 10 minutes) and does not cause decomposition of the material or degradation (even partial) of its properties. For example, the upper temperature limit is 190°C for FAPbI3 halide perovskite, 150°C for MAPbI3 perovskite, and 450°C for CsPbBr3 perovskite.

[0071] The most technologically advanced and efficient post-processing method is annealing at high temperature for a few minutes to an hour, in the temperature range optimal for the given material (perovskite ABX3 or perovskite-like phase) D, without exceeding the thermal stability range of this material.

[0072] Annealing was also performed during the chemical transformation to form phases that were stoichiometrically identical to the halide perovskites but had different structures. For example, after chemical transformation, a film of a FAPbI3 composition, such as the hexagonal phase of FAPbI3, was annealed at 160 °C for 30 min.

[0073] In one embodiment of the present invention, primary (monosubstituted, R-NH3 + ), quadratic (R1(R2)NH2 + ), cubic ([R1(R2)(R3)NH] + ), and the fourth order ([([R1(R2)(R3)NR4] + ) an interlayer or spacing organic cation E selected from a variety of substituted ammonium cations, such as ammonium cations; + Composition E2A comprising (n-1) B n X 3n+1 It is possible to obtain layered halide perovskites of the formula: In this case, halides or other salts of the corresponding cations or mixtures thereof are added to the composite reagent, which is then applied to the surface of the precursor layer of component B in step II of the process.

[0074] The ratio of components E and A in the composite reagent is selected to be close to that of the resulting layered perovskite. The component concentrations vary from 0.1M to 7M. ​​The halogen treatment in the third step of the process to produce a film of layered perovskite is carried out at temperatures between 25°C and 150°C, the optimum treatment temperature for this bulk cation-containing layered perovskite being close to the minimum temperature that results in the melting of the polyhalide of the desired substituted ammonium cation.

[0075] In one embodiment of the present invention, thin films of layered halide perovskites of compositions BA2PbI4, PEA2PbI4, BDAPbI4, (BMA)2PbI4, BA2MAPb2I7 were obtained by chemical conversion of pre-deposited Pb films of about 60 nm thickness by applying liquid complex reagents of different compositions. In particular, in step III, for BA2PbI4, a solution of butylammonium iodide with a concentration [BAI] = 0.9-1.1 M and a molar ratio [I2] / [BAI] = 0.5 was used as complex reagent. For PEA2PbI4, a solution of iodine and phenylethylammonium iodide (PEAI) with a concentration [PEAI] = 1.1 M and a molar ratio [I2] / [PEAI] = 0.5 was used as complex reagent. In BDAPbI4, a solution of iodine and butanediammonium iodide (BDAI2) with a concentration of 1.2 M and a molar ratio of [I2] / [BDAI]=0.5 was used as the composite reagent. In (BMA)2PbI4, a solution of iodine and butylmethylammonium (or butyl(methyl)azanium) iodide (BMAI) with a ratio of [BMAI]=1.1 M and [I2] / [BMAI]=0.5 was used as the composite reagent. In BA2MAPb2I7, a solution of iodine and butylammonium and methylammonium (MAI) iodide with a BAI concentration of 0.6 M, MAI concentration of 0.3 M, and an overall ratio of iodine to iodide close to 0.5 was used as the composite reagent. In step III, the film obtained as described above was treated with halogen (I2) vapor for 5 min at a temperature of 50 °C or higher. These examples show that layered halide perovskites containing various substituted ammonium cations can be obtained under substantially identical conditions. It should be noted that the conditions required for the preparation of layered perovskites also do not depend on the type of substituents on the organic cation. EXAMPLES

[0076] The table below gives typical conditions for the formation of the films and the efficiency of devices based on them (if fabricated).

[0077] The first column P[D] denotes the precursor of component B. The optimal thickness of that layer is about 60-65 nm for metal films (Pb, Sn, Bi or their alloys, or layered structures containing multiple layers of stacked metals (Pb, Sn, Bi)).

[0078] The second column shows the ratio [X2] / [AX] and the concentration of AX in the composite reagent applied. In all cases except for the application of pure AX applied from a vapor, the composite reagent was used in the form of an organic solvent containing solution of X2 and AX.

[0079] The third column indicates the conditions for post-processing (eg, annealing) of films obtained by applying the reagents indicated in the second column to films of precursor B.

[0080] The fourth column indicates the halogen (X2) treatment conditions of the precursor film formed after step II.

[0081] The fifth column indicates the conditions for the final treatment (annealing) of the film obtained after completion of step III (treatment with X2), which is essential to remove excess halogen and complete the formation of the ABX3 layer.

[0082] The sixth column shows the phases of the resulting materials by X-ray phase analysis.

[0083] The seventh column shows the average particle size of the resulting organic-inorganic metal-halide perovskite-like compounds.

[0084] The eighth column shows the PCE (%) of the fabricated solar cells containing the resulting films of organic-inorganic metal-halide perovskite-like compounds as light absorbing layers.

[0085] [Table 1]

[0086] Table 1 and Figure 2 show data on the average size of perovskite particles in MAPbI3 films and the efficiency of solar cells containing the corresponding perovskite films as light absorbing layers depending on their preparation conditions. From the presented data the following conclusions can be drawn:

[0087] When MAI is applied to the lead surface without the iodine additive in step II, no chemical reaction occurs and no nucleation of perovskite particles occurs. Treatment with iodine results in the formation of a polyiodide melt, which quickly reacts with metallic lead to form numerous small perovskite particles. As a result, the resulting perovskite film has a relatively small grain size and exhibits relatively low efficiency values ​​when used as a light absorbing layer in a solar cell.

[0088] In step II, when the composite reagent with the ratio [X2] / [AX]=1 is applied to the lead surface, a MAPbI3 perovskite film with a given grain size is instantly formed, and subsequent treatment with halogen does not result in reactive growth. As a result, the obtained perovskite film has an average grain size of about 500 nm and shows relatively low efficiency values ​​(maximum 12%) when used as a light absorbing layer in solar cells.

[0089] In step II, a "precursor film" containing seeds (nuclei) of perovskite-like phase is formed when a composite reagent with a molar ratio [X2] / [AX]=0.5 is applied to the surface of the metal (Pb) layer. The precursor film is then treated with iodine, after which perovskite particles grow by chemical reaction. As a result, the obtained perovskite film has a large average particle size (around 700-800 nm) and shows high efficiency values ​​(up to 16%) when used as a light absorbing layer in solar cells.

[0090] Thus, the experimental data obtained directly demonstrates that the introduction of an intermediate step in the processing of perovskite-like compound films reliably forms perovskite-like phase seeds as well as precursor films containing the initial reagents AX and B. This is a key step in forming perovskite films with increased average grain size, leading to improved efficiency of the resulting perovskite solar cells.

[0091] Different A + Cation and X - To obtain perovskite-like compounds containing anions (Table 1), not only the ratio [X2] / [AX] is important, but also the ratio of different cations and anions in the applied composite reagent. In one embodiment, composition MA 0.25 FA 0.75 To obtain a PbI3 film, [MA + ] / [FA + A composite reagent having a molar ratio of about 3 was used. Composition MA 0.25 FA 0.75 PbBr 0.5 I 2.5 To obtain a membrane of about 3 [MA + ] / [FA + ] molar ratio, and a molar ratio of about 5 [I - ] / [Br - ] was used. That is, different A + Different ratio of cations to x - The ratio of the anions should be selected to be close to their desired ratio in the resulting film of the organic-inorganic metal-halide compound having a perovskite-like structure.

Claims

1. A method for preparing a semiconductor film of an organic-inorganic metal-halide compound having a perovskite-like structure, said method comprising the steps of: a) applying a layer of a precursor comprising component B onto a substrate; b) applying a layer of a composite reagent on the surface of the layer of the precursor containing the component B to form a film composed of the layer of the precursor containing the component B and the layer of the composite reagent applied on the surface of the precursor; c) treating the film on the substrate by exposure to additional reagent X 2 for a time necessary and sufficient for completion of a chemical reaction between the composite reagent applied in step b) and the precursor comprising component B, thereby resulting in the formation of an organic-inorganic metal-halide perovskite-like compound; The composite reagent applied in step b) is [X 2 ] / [AX] molar ratio is 0<[X 2 ] / [AX]<1, and the film obtained after step b) contains seeds of a phase having a perovskite-like structure, The component B is a cation M of at least one metal (Pb, Sn, Bi, etc.) selected from Pb, Sn, Bi, and mixtures thereof. n+ Including, The reagent AX is a cation A + and anion X - wherein the cation A is a salt containing + is a monovalent organic cation or a combination of an organic cation and an inorganic cation; The organic cation is methylammonium CH 3 N.H. 3 + , formamidinium (NH 2 ) 2 CH + , Guanidinium C(NH 2 ) 3 + and substituted ammonium cations, such as mono- or di- or tri- or tetra-substituted ammonium cations, and combinations thereof; the inorganic cation is selected from Cs + , Rb + and unsubstituted (NH 4 + ), and combinations thereof; The anion X - But Cl - , B - , I - or pseudohalide anions, and combinations thereof; Reagent X 2 is a molecular halogen.

2. The film containing the perovskite-like seeds is treated with Reagent X. 2 2. The method according to claim 1, wherein in step b) before the treatment with , a heat treatment is carried out at a temperature of 30 to 300° C. for 1 to 3600 seconds.

3. After completion of step c), the resulting film of the organic-inorganic metal-halide compound having a perovskite-like structure is Heat treatment at a temperature of 30 to 400° C. for 1 to 7200 seconds, or exposure to inert gases, dry air, moist air, or solvent vapors; or exposure to visible, ultraviolet, or infrared light; or treatment with a solution or solvent; or subjected to additional post-treatment, including a combination of these types of post-treatment, 2. The method of claim 1, wherein the exposure to solvent vapors and treatment with the solution or solvent can achieve at least one of the following: removal of excess halogen adsorbed by the film, removal of possible by-products of chemical transformation, or improvement of functional properties of the perovskite layer.

4. The method of claim 1, wherein the film of step b) is formed by repeatedly applying the composite reagent.

5. The composite reagent applied in step b) is uniformly distributed on the surface of the precursor layer containing component B using inkjet printing, screen printing, spin coating, dip coating, aerosol spraying, in particular ultrasonic spraying, spraying through a nozzle, electrospraying, aerosol inkjet printing, and the composite reagent is a mixture of component A and component B. + and X - Or Reagent AX and Reagent X 2 10. The method of claim 1, wherein the active material is a solution or melt of any one of the above substances, as well as a colloid or suspension or emulsion comprising these substances in the liquid or solid phase and with the addition of one or more solvents.

6. 2. The method according to claim 1, wherein in step a) the precursor film comprising component B is obtained in the form of a layered structure comprising a plurality of layers of metals selected from Pb, Sn, Bi or alloys thereof, or of stacked metals (Pb, Sn, Bi), and also in the form of a film of an oxide or a lead salt, the precursor comprising component B being applied by vacuum deposition or electrochemical deposition, chemical vapor deposition or by decomposition of a previously applied solid phase compound comprising component B.

Citation Information

Patent Citations

  • Manufacturing system and method for perovskite films based on multi-source deposition

    JP2017526176A

  • Method for forming perovskite film, perovskite film, and solar cell

    JP2018522394A

  • Method of obtaining light absorbing material with perovskite-like structure

    RU2675610C1

  • Method of obtaining light absorbing material with perovskite-like structure

    RU2685296C1

  • Process for the preparation of halide perovskite and perovskite-related materials

    WO2017195191A1